Knowledge, attitude and practices of consumers in e-commerce transactions - Abu Bakar, Elistina; Lim, Li Chang; Saidin, Aznan Zuhid (IEEE, 2013)
E-commerce is a trading system between suppliers and consumers through the electronic medium which gives lots of benefits to both parties. On the other hand, it will also cause several problems to consumers such as the issue of privacy and security. The main purpose of this paper is to describe and identify the level of knowledge, attitude and practices of consumers in e-commerce transactions in four residential areas in Muar Johore. The totals of 104 respondents who had practiced e-commerce were systematically randomly selected. Questionnaires were used as a tool for collecting data and the Statistical Package for Social Sciences (SPSS) had been utilised for data analysis. The results show that there was significant relationship between the consumers' knowledge and consumer purchasing practices of-e-commerce (r=0.251*, p<;0.05). It means the higher the level of knowledge, the better the practices and vice versa. The study also shows that there was significant correlation between consumers' attitude and their practices in e-commerce purchasing (r=0.197*, p<;0.05). Therefore, if the consumers' attitude towards e-commerce is positive, it is more likely that they will engage in e-commerce transaction. For policy implication, government should continue promoting and enhancing consumers' awareness and knowledge with the introduction of government policies which are beneficial to consumers.